Estado actual del cultivo de la cebolla blanca (Allium cepa L.) en la zona de García Moreno, Cantón Bolívar, Provincia del Carchi - Cuases Chingal, Ana Lucia (2018)
VII. SUMMARY This research work was carried out in the agricultural area of the community since it presents a problem in the cultivation of beans that is Anthracnose, the purpose was to identify the factors that affect the development of this disease, the same ones that create environments of susceptibility presenting favorable conditions for the dissemination and establishment of this pathogen that causes irreversible damage to the plants, decreasing their production. This diagnosis was made directly with farmers who have dedicated their whole lives to agriculture and bean production. To carry out this research, the survey technique was applied specifically in the place of cultivation, based on their experiences to determine the causes that produce this problem. After the tabulation and its results, it was determined that in order to the disease be spread there is an interaction of a number of factors such as: infected seed, previous stubbles, insects and environmental conditions like constant rains accompanied by winds, excess humidity and temperatures which are optimal conditions for the establishment of Anthracnose. The importance of this research served as a basis for greater knowledge about the causes and in turn the consequences that subsequently generate problems for crops and producers in general, since they are subject to environmental conditions, as well as being able to implement better strategies of integrated management that allows them to reduce or in turn the eradication of anthracnose in their crops.